Beyond Cinematic Stereotypes: Using Religion to Gender Film Characters in Alternative Ways Journal for Religion, Film and Media - Sofia Sjö (Journal for Religion, Film and Media, 2016)
In films, religious characters are often gendered in quite traditional ways, but there are some notable exceptions. This article discusses two Scandinavian films that partly break this mold. The analysis illustrates how in films different forms of religion are gendered quite differently, and explores the way in which religious themes can open up for alternative male and female characters. Different ways of understanding the representations are discussed and related to views on the place and role of religion in the Scandinavian context today. The article draws on the mediatization of religion theory as a theoretical framework, but also highlights the challenges that complex images of gender and religion pose to this theory.